- #1
Petrus
- 702
- 0
Hello MHB,
given a linear transformation F so that this is known
\(\displaystyle \left\{
\begin{aligned}
\phantom{1}F(1,0,0)=(1,2,3) \\
F(1,1,0)=(0,0,1)\\
F(1,1,1)=(12,3,4)\\
\end{aligned}
\right.\)
Decide F
progress:
\(\displaystyle F(e_1)=(1,2,3)\)
\(\displaystyle F(e_2)=F(e_1)+F(e_2)-F(e_1)=(0,0,1)-(1,2,3)=(-1,-2,-2)\)
\(\displaystyle F(e_3)=F(e_1)+F(e_2)+F(e_3)-(F(e_1)+F(e_2))= (12,3,4)-(-1,-2,-2)=(13,5,6)\)
My \(\displaystyle f(e_3)\) is wrong acording to facit and I don't understand
Regards,
\(\displaystyle |\pi\rangle\)
given a linear transformation F so that this is known
\(\displaystyle \left\{
\begin{aligned}
\phantom{1}F(1,0,0)=(1,2,3) \\
F(1,1,0)=(0,0,1)\\
F(1,1,1)=(12,3,4)\\
\end{aligned}
\right.\)
Decide F
progress:
\(\displaystyle F(e_1)=(1,2,3)\)
\(\displaystyle F(e_2)=F(e_1)+F(e_2)-F(e_1)=(0,0,1)-(1,2,3)=(-1,-2,-2)\)
\(\displaystyle F(e_3)=F(e_1)+F(e_2)+F(e_3)-(F(e_1)+F(e_2))= (12,3,4)-(-1,-2,-2)=(13,5,6)\)
My \(\displaystyle f(e_3)\) is wrong acording to facit and I don't understand
Regards,
\(\displaystyle |\pi\rangle\)